2020
DOI: 10.1186/s12889-020-09194-3
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards reducing sociodemographic disparities in breastfeeding outcomes in Indonesia: a trend analysis from 2002 to 2017

Abstract: Background: Improving breastfeeding practice is important for reducing child health inequalities and achieving several Sustainable Development Goals. Indonesia has enacted legislation to promote optimal breastfeeding practices in recent years. We examined breastfeeding practices among Indonesian women from 2002 to 2017, comparing trends within and across sociodemographic subgroups. Methods: Data from four waves of the Indonesia Demographic and Health Surveys were used to estimate changes in breastfeeding pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
4
11
0
2
Order By: Relevance
“…Urban mothers had higher knowledge regarding breastfeeding compared with suburban mothers. However, rural mothers had a more favorable attitude towards breastfeeding when compared with urban mothers [20,21].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Urban mothers had higher knowledge regarding breastfeeding compared with suburban mothers. However, rural mothers had a more favorable attitude towards breastfeeding when compared with urban mothers [20,21].…”
Section: Discussionmentioning
confidence: 88%
“…These ndings were similar to a study done by Vinutha, the results indicated that rural mothers practiced early initiation of breastfeeding, Exclusive Breast Feeding (EBF) for the rst six months, and longer duration of breastfeeding when compared with suburban mothers. The rate of not feeding colostrum was high in the urban area when compared to rural mothers [20,21]. Another study found a statistically signi cant association existed between age, education, and socio-economic status of respondents with their knowledge of primipara mothers the study found a signi cant difference between mothers' practices in Erbil city and Koy-Sanjaq city; The current study reveals a signi cant difference between practice among mothers in Erbil city and Koy-Sanjaq, also signi cant difference was found between Koy Sanja and Shaqlawa city concerning achieved colostrum feeding, while there were signi cant differences was found between mothers in Erbil city and Shaqlawa city, Shaqlawa and Koy-Sanjaq city mothers with non-difference between Shaqlawa city and Koy-Sanjaq city mothers regarding knowledge about colostrum feeding.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…22 The downward trend of pre-lacteal feeding in the last decade was followed by the increasing prevalence of early initiation or exclusive breastfeeding. 14,23 However, there were still more than half of the children not exclusively breastfeed. Therefore, more effort to improve the exclusive type or infant feeding practices should be prioritized.…”
Section: Discussionmentioning
confidence: 99%